Antimicrobial, Antioxidant and Cytotoxic Constitutents from Roots of Rumex crispus Linn† - V. RAO, CHIRRAVURI; SIVARAMAKRISHNA, CHILLARA; MALLIKHARJUNARAO, CHUNDI; JAYALAKSHMI, RAVI; B. SHAIK, DILSHAD; V. SUBBARAJU, GOTTUMUKKALA (Asian Journal of Chemistry, 2010)
Anthraquinone derivatives (1-5,7) and stilbene derivative (6) were isolated from the roots of Rumex crispus. The extracts as well as pure compounds (1-7) have shown remarkable antimicrobial, antioxidant and cytotoxic activites. Compound 6 displayed significant antifungal activity and compound 3 exhibited potent brine shrimp lethality activity.